Mycorrhizal fungal biomass and scavenging declines in phosphorus-impoverished soils during ecosystem retrogression. (January 2016) - Teste, François P.; Laliberté, Etienne; Lambers, Hans; Auer, Yasha; Kramer, Susanne; Kandeler, Ellen
Abstract: Mycorrhizal fungi enhance plant phosphorus (P) acquisition via their extraradical hyphae (ERH) that scavenge nutrients outside root depletion zones. While soil P availability declines during ecosystem retrogression, how ERH biomass and scavenging vary during ecosystem retrogression remains unknown; it is expected to increase if plants allocate more carbon (C) to mycorrhizal fungi as P availability declines. We measured fungal and bacterial biomass using in-growth cores and lipid biomarkers along a 2-million-year dune chronosequence in an Australian biodiversity hotspot showing a ∼60-fold decline in total soil P concentration with increasing soil age. We compared the levels of key fungal biomarkers (ergosterol, NLFA 16:1ω5, and PLFA 18:2ω6, 9) between closed, mesh, and open cores during five months (four sampling dates including the wet winter months), thus allowing us to also determine the dynamics of mycorrhizal fungal scavenging. We found strikingly low and declining biomass of ERH with declining P availability, with minimal long-distance scavenging by ERH. Biomass of ERH was highest in the younger ( c . 1 ka) soils that were comparatively rich in P and other nutrients. By contrast, the oldest, most P-impoverished soils had the lowest biomass of ERH, despite high mycorrhizal root colonisation, and high abundance and diversity of potential plant hosts. We show that extremely low P availability constrains ERH biomass. Such low mycorrhizal fungal biomass highlights the need for a more 'mycocentric' view of plant–mycorrhizal relationships in old, severely P-impoverished ecosystems. Highlights: Low soil phosphorus (P) availability appears to limit biomass of soil biota. Mycorrhizal scavenging is driven by nutrient availability and soil age. A 'mycocentric' view of plant–soil relationships in P-impoverished ecosystems is needed.